2008
DOI: 10.1177/089686080802805s08
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Renin–angiotensin System Inhibition on Regression of Encapsulating Peritoneal Sclerosis

Abstract: Background Encapsulating peritoneal sclerosis (EPS) is a clinical syndrome associated with symptoms of ileus and irreversible sclerosis of both visceral and parietal peritoneum. Peritoneal dialysis (PD) patients rarely develop EPS, a severe life-threatening condition of unknown pathogenesis. Angiotensin II is known to promote fibrosis and inflammation in various tissues. Renin–angiotensin system (RAS) blockade provides advantages in the course of diseases such as hypertension, chronic kidney disease, and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A renin-angiotensin system inhibitor could be a powerful tool in preventing the progression of PF. Angiotensin receptor blockers or angiotensin converting-enzyme inhibitors have been shown to ameliorate chlorhexidine gluconate-induced PF in rats [27]. Aliskiren inhibits angiotensin I generation from angiotensinogen by direct renin inhibitors and further decreases angiotensin II production [12].…”
Section: Discussionmentioning
confidence: 99%
“…A renin-angiotensin system inhibitor could be a powerful tool in preventing the progression of PF. Angiotensin receptor blockers or angiotensin converting-enzyme inhibitors have been shown to ameliorate chlorhexidine gluconate-induced PF in rats [27]. Aliskiren inhibits angiotensin I generation from angiotensinogen by direct renin inhibitors and further decreases angiotensin II production [12].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of valsartan in preventing the development SEP has been demonstrated in two studies (5,17). One study demonstrated that valsartan therapy significantly decreased parietal peritoneal thickness and the number of dialysate inflammatory cells, whereas there was no noticeable improvement in other histological outcomes such as neovascularization and fibrosis (17). Another study established that the use of high‐dose valsartan in the experimental model of peritoneal fibrosis reduced the production of dialysate TGF‐β1 and repressed the thickening of the visceral peritoneum (5).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, such molecules as prorenin, renin and aldosterone occurring in the intermediate steps of RAAS were found to increase fibrosis independently of angiotensin II (15,16). In the literature, some authors have suggested that ACE inhibitors and angiotensinogen receptor blockers including olmesartan medoxomil and valsartan may prevent the development of peritoneal fibrosis (17,18). However, there were insufficient data to assess the impact of aliskiren on peritoneal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations